2007
DOI: 10.1007/s00198-007-0385-1
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the metabolic syndrome and bone health in older men and women: the Rancho Bernardo Study

Abstract: Associations between the metabolic syndrome and bone health in older men and women: the Rancho Bernardo Study MS may be another risk factor for osteoporotic fractures. The association of MS with higher BMD was explained by the higher BMI in those with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
171
5
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(198 citation statements)
references
References 34 publications
16
171
5
6
Order By: Relevance
“…Presence of risk factors for the metabolic syndrome is associated with both higher blood pressures with higher salt intake 50 and higher fracture risk. 51 Metabolic syndrome has been associated with decreased production of NO, and NaCl has been shown to dose dependently decrease endothelial NO synthase activity in endothelial cells. 52 NO synthases have been demonstrated in both osteoclasts and osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of risk factors for the metabolic syndrome is associated with both higher blood pressures with higher salt intake 50 and higher fracture risk. 51 Metabolic syndrome has been associated with decreased production of NO, and NaCl has been shown to dose dependently decrease endothelial NO synthase activity in endothelial cells. 52 NO synthases have been demonstrated in both osteoclasts and osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, the Rancho Bernardo Study reported that metabolic syndrome was not only associated with a lower BMD, but it was also associated with an increased incidence of osteoporotic fractures. 22 Hyperglycemia may have a direct adverse effect on bone metabolism because glucose enhances osteoclast activity in vitro. 23 One study conducted with 238 subjects who had received their first solid organ transplantation and 873 controls showed an odds ratio of 1.94 (95% CI 1.5-2.6) for fracture on individuals with pre-transplant diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that vertebral BMD was significantly lower in women with MetS among 2475 Korean women after adjustment for age, weight and height, 21 and the incidence of osteoporotic non-vertebral fractures was higher in women with MetS in the Rancho Bernardo Study. 22 Therefore, although BMD may be associated with both sarcopenia and MetS, it has not been determined whether the interaction between sarcopenia and MetS further increases total and regional BMD as determined by dual-energy X-ray absorptiometry (DXA).…”
Section: Introductionmentioning
confidence: 99%